A positive bacterial culture during re-implantation is associated with a poor outcome in two-stage exchange arthroplasty for deep infection. (November 2017) - Akgün, D.; Müller, M.; Perka, C.; Winkler, T.
Abstract : Aims: The aim of this study was to identify the incidence of positive cultures during the second stage of a two-stage revision arthroplasty and to analyse the association between positive cultures and an infection-free outcome. Patients and Methods: This single-centre retrospective review of prospectively collected data included patients with a periprosthetic joint infection (PJI) of either the hip or the knee between 2013 and 2015, who were treated using a standardised diagnostic and therapeutic algorithm with two-stage exchange. Failure of treatment was assessed according to a definition determined by a Delphi-based consensus. Logistic regression analysis was performed to assess the predictors of positive culture and risk factors for failure. The mean follow-up was 33 months (24 to 48). Results: A total of 163 two-stage revision arthroplasties involving 84 total hip arthroplasties (THAs) and 79 total knee arthroplasties (TKAs) were reviewed. In 27 patients (16.6%), ≥ 1 positive culture was identified at re-implantation and eight (29.6%) of these subsequently failed compared with 20 (14.7%) patients who were culture-negative. The same initially infecting organism was isolated at re-implantation in nine of 27 patients (33.3%). The organism causing re-infection in none of the patients was the same as that isolated at re-implantation. The risk of the failure of treatment was significantly higher in patients with a positive culture (odds ratio (OR) 1.7; 95% confidence interval (CI) 1.0 to 3.0; p = 0.049) and in patients with a higher Charlson Comorbidity Index (OR 1.5; 95% CI 1.6 to 1.8; p = 0.001). Conclusion: Positive culture at re-implantation was independently associated with subsequent failure. Surgeons need to be aware of this association and should consider the medical optimisation of patients with severe comorbidities both before and during treatment. Cite this article: Bone Joint J 2017;99-B:1490–5.